Reconstructing the First Metatarsophalangeal Joint of Homo naledi - Fan, Yuxuan; Antonijević, Djorđje; Antic, Svetlana; Li, Ruining; Liu, Yaming; Li, Zhiyu; Djuric, Marija; Fan, Yifang (Frontiers in Bioengineering and Biotechnology, 2019)
The aim of the present study was to develop a new method to reconstruct damaged metatarsophalangeal joint (MTPJ) of Homo naledi's fossil and to deepen the understanding of the first metatarsal head (FMH) morphological adaptation in different gait patterns. To this purpose three methods were introduced. The first served to compare the anthropometric linear and volumetric measurements of Homo naledi's MTPJ to that of 10 various athletes. The second was employed to measure curvature diameter in FMH's medial and lateral grooves for sesamoid bones. The third was used to determine the parallelism between medial and lateral FMH grooves. The anthropometric measurements of middle-distance runner to the greatest extent mimicked that of Homo naledi. Thus, it was used to successfully reconstruct the damaged Homo naledi's MTPJ. The highest curvature diameter of medial FMH groove was found in Homo naledi, while in lateral FMH groove it was the highest in volleyball player, suggesting their increased bear loading. The parallelism of medial and lateral FMH grooves was observed only in Homo naledi, while in investigated athletes it was dis-parallel. Athletes' dis-paralleled structures make first MTPJ simple flexion movement a complicated one: not rotating about one axis, but about many, which may result in bringing a negative effect on running. In conclusion, the presented method for the reconstruction of the damaged foot bone paves the way for morphological and structural analysis of modern population and fossil hominins' gait pattern.